The Relationship Between Pamong Teacher Guidances and The Succes of Student Educational Field Practice (PLK) - Jufri, Windry Novalia; Lestari, Yuannissa Ulimaz Jayana (CIVED, 2024)
The research problem background is the low of two-way communication between PLK students and tutor teachers, so that students have difficulty in dealing with the obstacles encountered during PLK at school. Based on this research, researchers are interested in doing research that purpose to reveal the relationship between Teacher Guidance and Student PLK Success. This research type was quantitative research through method in correlational. This research was done at the Civil Engineering Department, Engineering Faculty, Universitas Negeri Padang. The research respondents were Building Engineering Education Study Program students, Engineering Faculty, Universitas Negeri Padang who had followed in the PLK period July-December 2022. The technique for sampling used Total Sampling with a sample size of 45 respondents. The method for data collection uses a questionnaire and documentation of PLK grades filled in by the mentor teacher. The technique for analysis used is Product Moment correlation. The research results indicated that there is a positive and significant relationship between Teacher Guidance and Student PLK Success. The evidence was the correlation coefficient greater than r table which is 0.705 > 0.294 and a value of significance is 0.00 < 0.05.